Evaluation of GeneXpert MTB/RIF for detection of pulmonary tuberculosis at peripheral tuberculosis clinics. (April 2017) - Shao, Yan; Peng, Hong; Chen, Cheng; Zhu, Tao; Ji, Ming; Jiang, Wei; Zhu, Wei; Zhai, Xiang Jun; Lu, Wei
Abstract: Tuberculosis is one of the most common infectious diseases in China, while delayed patient finding obstructed disease control, especially for smear-negative patients. The current study was undertaken to evaluate the diagnostic accuracy of GeneXpert MTB/RIF compared with conventional methods in the detection of pulmonary tuberculosis patients. A total of 295 spot sputum samples from confirmed pulmonary tuberculosis patients were evaluated from September 2014 to June 2015. Each sample was examined by acid-fast bacillus smear microscopy, culture and GeneXpert MTB/RIF. The sputum culture on Löwenstein-Jensen (L-J) was considered as the gold-standard. After testing by smear, 68.81% (203/295) was negative and 31.19% (92/295) was positive. As the gold-standard, L-J culture detected 37.97% (112/295) positive of all specimens, while the positivity for GeneXpert MTB/RIF was 46.44% (137/295). Compared with L-J culture, the combined sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for GeneXpert MTB/RIF were 94.64%, 82.97%, 77.37% and 96.18% respectively. For smear-negative specimens, the sensitivity, specificity, PPV and NPV for GeneXpert MTB/RIF were 96.00%, 83.05%, 44.44% and 99.32%; while for smear-positive specimens, the corresponding accuracy values were 94.25%, 80.00%, 98.80% and 44.44%. The findings of study indicated that GeneXpert MTB/RIF assay demonstrated a high sensitivity in detecting Mycobacterium tuberculosis compared to smear method and a high NPV among smear negative patients. Highlights: Evaluate the diagnostic accuracy of GeneXpert MTB/RIF at peripheral clinics in Jiangsu Province for the first time. Indicate a high sensitivity of GeneXpert MTB/RIF in detecting Mycobacterium tuberculosis compared to smear microscopy. GeneXpert MTB/RIF could be applicable for case finding and validation of smear-negative cases because of the high NPV.